A doped manganese iron phosphate precursor, preparation method and manganese iron phosphate lithium positive electrode material

By doping vanadium ions and using quaternized modified sodium lignin sulfonate dispersant, the problems of poor conductivity and low rate performance of lithium manganese iron phosphate positive electrode material are solved, and the material's rate performance and conductivity are significantly improved.

CN119218967BActive Publication Date: 2025-02-11HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411732280.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The lithium manganese iron phosphate positive electrode material has poor conductivity and low rate performance, resulting in poor reversibility and poor electrochemical stability of the material.

Method used

By doping vanadium ions and using quaternized modified sodium lignin sulfonate as a dispersant, the grain refinement and dispersion of the precursor of manganese phosphate are improved, thereby improving the diffusion efficiency of lithium ions and the electronic conductivity of the material.

Benefits of technology

The rate performance and conductivity of lithium manganese iron phosphate cathode material are significantly improved, the structural stability and cyclic properties of the material are improved, and the dissolution of manganese is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a doped ferromanganese phosphate precursor, a preparation method and a lithium ferromanganese phosphate positive electrode material, belonging to the technical field of lithium ion batteries. The invention adopts a hydrothermal method to prepare a doped ferromanganese phosphate precursor and a lithium ferromanganese phosphate positive electrode material, and refines the grain size by doping vanadium ions, improves the diffusion rate and conductivity of lithium ions, and enhances the rate performance and electronic conductivity of the positive electrode material. In addition, in the preparation process, quaternary ammonium modified sodium lignin sulfonate is used as a dispersant to improve the dispersibility between particles, solve the problem that the particle size is too small due to vanadium doping, the particles agglomerate, and then the electrochemical performance of the positive electrode material decreases. The molecular chain of the quaternary ammonium modified sodium lignin sulfonate also contains dithiocarboxyl groups, which can reduce and fix manganese ions while improving the dispersibility of the dispersant, improve structural stability, and reduce the dissolution of manganese.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a doped ferromanganese phosphate precursor, a preparation method and a lithium ferromanganese phosphate positive electrode material. Background Art

[0002] Compared with traditional lead-acid batteries, nickel-metal hydride batteries, nickel-cadmium batteries and other secondary batteries, lithium-ion batteries have the advantages of light weight, high voltage, high specific energy, long cycle life, no memory effect and low environmental pollution. They have been widely used in many fields such as daily life, new energy vehicles and energy storage. Among them, lithium iron phosphate has become one of the most commonly used positive electrode materials in lithium-ion batteries due to its high safety and low cost. However, the low electrochemical working platform of lithium iron phosphate limits its energy density upper limit, making it difficult to adapt to and meet the current demand for long-term lithium-ion batteries. As another phosphate positive electrode material, lithium manganese phosphate has a higher energy density, but its lithium ion diffusion rate is low. Lithium manganese iron phosphate combines the advantages of lithium iron phosphate and lithium manganese phosphate, significantly improving the energy density while ensuring the high safety of the material.

[0003] However, lithium iron manganese phosphate cathode materials still have defects such as low electronic conductivity and small lithium ion diffusion coefficient. These problems lead to poor reversibility and poor rate performance of lithium iron manganese phosphate materials. Currently, the most commonly used methods are carbon coating and metal ion doping to improve the conductivity and electrochemical properties of lithium iron manganese phosphate cathode materials. However, both of these modification methods have certain defects. For example, in the process of metal ion doping modification, uneven mixing or large differences in ion radius will lead to uneven dispersion and too small particle size, which will cause manganese elements to dissolve easily during the cycle charge and discharge process. The structure of the lithium iron manganese phosphate cathode material is unstable, which ultimately affects the electrochemical stability of the lithium iron manganese phosphate cathode material and makes it difficult to significantly improve the conductivity and rate performance of the lithium iron manganese phosphate cathode material. Summary of the invention

[0004] The object of the present invention is to provide a doped ferromanganese phosphate precursor, a preparation method and a lithium ferromanganese phosphate positive electrode material to solve the problems of poor conductivity and low rate performance of the lithium ferromanganese phosphate positive electrode material.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a doped ferromanganese phosphate precursor, comprising the following process steps:

[0007] S101. Adding an iron source, a manganese source and a phosphorus source to deionized water to form a first mixed solution;

[0008] S102. Adding the dispersant and the vanadium source to deionized water to prepare a second mixed solution;

[0009] S103. Raise the temperature of the first mixed solution to 40-45°C, add the second mixed solution dropwise while stirring, stir and react for 1-2 hours, and then hydrothermally react at 180-220°C for 6-7 hours;

[0010] S104. The hydrothermal reaction product is filtered, washed and dried to obtain a ferromanganese phosphate precursor;

[0011] The dispersant is quaternary ammonium modified sodium lignin sulfonate; the molecular chain of the quaternary ammonium modified sodium lignin sulfonate contains dithiocarboxyl groups.

[0012] Preferably, the molar ratio of the phosphorus source, the iron source, the manganese source and the vanadium source is 1: (0.3-0.7): (0.3-0.7): (0.02-0.04).

[0013] Preferably, the vanadium source includes a combination of one or more of vanadium nitrate, vanadium pentoxide, ammonium metavanadate, vanadium chloride, sodium orthovanadate and hydrated vanadyl sulfate.

[0014] Preferably, the added amount of the dispersant is 8-12% of the total mass of the iron source, the manganese source and the phosphorus source.

[0015] Preferably, the phosphorus source includes a combination of one or more of phosphoric acid, diammonium dihydrogen phosphate, diammonium hydrogen phosphate, dipotassium hydrogen phosphate, pyrophosphoric acid, sodium phosphate, iron phosphate and manganese phosphate.

[0016] Preferably, the iron source comprises a combination of one or more of ferric nitrate, ferric carbonate, ferric phosphate, iron powder, ferric oxide, ferrous oxalate dihydrate, ferrous nitrate and ferrous acetate.

[0017] Preferably, the manganese source includes a combination of one or more of manganese dioxide, manganese tetraoxide, manganese carbonate, manganese oxalate, manganese phosphate, manganese dichloride and manganese sulfate.

[0018] By adopting the above technical scheme, the doped ferromanganese phosphate precursor of the present invention is doped with vanadium ions, and a small amount of vanadium ions can replace part of the iron ions in the preparation process of the precursor, participate in the formation process of the ferromanganese phosphate precursor, and enter the lattice of the ferromanganese phosphate precursor. Vanadium ions have a smaller ionic radius than iron ions, which can reduce the volume of the unit cell formed, and the particle size is gradually refined, which helps to shorten the diffusion distance of lithium ions inside the particles, widen the deintercalation channel of lithium ions in the lattice, improve the diffusion efficiency of lithium ions, and reduce the diffusion energy of lithium ions, thereby showing excellent rate performance. At the same time, the valence state of vanadium is higher than that of iron ions, which can cause crystal charge defects, and the defects can be compensated by electronic compensation mechanisms, while also contributing to the improvement of the electronic conductivity of the material.

[0019] A small amount of doping with vanadium ions helps the vanadium ions to exist in the form of tetravalent vanadium ions, which have a high solid solubility with ferromanganese phosphate, thereby smoothly realizing the doping of vanadium ions. However, when the amount of vanadium ions added increases, some vanadium ions will exist in the form of metavanadate, which will be unfavorable for improving the lithium ion diffusion rate, and thus affect the improvement of the electrochemical performance of the positive electrode material.

[0020] The introduction of vanadium ions can refine the grain size and improve the rate performance and electronic conductivity of the cathode material. However, as the particle size of the vanadium-doped ferromanganese phosphate precursor gradually increases, it will become increasingly difficult to control the particle growth. The precursor will undergo significant agglomeration during the preparation process, and many particles will exist in the form of agglomerates, and the particle size will not be uniform. The electron transmission and ion migration capabilities of the resulting precursor particles will decrease, leading to a decrease in electrochemical performance. In addition, the increase in the degree of refinement will also cause manganese to be easily dissolved during the charge and discharge cycle, thereby affecting the rate performance of the cathode material.

[0021] Therefore, a dispersant is added during the vanadium ion doping process. The dispersant of the present invention adopts quaternized ammonium modified sodium lignin sulfonate. Sodium lignin sulfonate is a biomass dispersant and will not affect the electrochemical properties of the ferromanganese phosphate precursor. However, since the molecular weight of sodium lignin sulfonate itself is not large and the dispersion stability is poor, the present invention first modifies the sodium lignin sulfonate.

[0022] The sodium lignin sulfonate modified by quaternization has amphoteric properties. The introduced cationic groups can help form stronger electrostatic repulsion on the particle surface. The large volume groups introduced by quaternization can also provide additional steric hindrance to prevent direct contact between particles, effectively prevent particle agglomeration, improve the dispersion performance of sodium lignin sulfonate, and thus effectively avoid the agglomeration phenomenon of vanadium-doped ferromanganese phosphate precursor. In addition, the quaternization-modified sodium lignin sulfonate can slow down the nucleation rate, affect the growth mode of particles by changing the interfacial tension in the solution, promote uniform growth of particles, effectively control the particle size, improve the dispersibility of particles, and finally obtain a ferromanganese phosphate precursor with uniform particle size and uniform distribution.

[0023] The quaternary ammonium modified sodium lignin sulfonate of the present invention also contains a dithiocarboxyl group on its molecular chain, which can not only increase the steric hindrance effect of the dispersant, improve the dispersibility and stability of the dispersant, but also reduce the iron ions and manganese ions in the system to a stable divalent state, thereby improving the structural stability of the obtained manganese iron phosphate precursor; and can fix the manganese ions, prevent the migration and dissolution of the manganese ions, significantly reduce the dissolution of manganese, and improve the rate performance of the positive electrode material.

[0024] Preferably, the raw materials of the quaternized modified sodium lignin sulfonate include sodium lignin sulfonate, a quaternizing agent and carbon disulfide in a mass ratio of 1: (0.6-0.8): (0.25-0.35).

[0025] Preferably, the quaternizing agent is a combination of one or more of 3-chloro-2-hydroxypropyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride and hexadecyltrimethylammonium bromide.

[0026] Preferably, the quaternary ammonium modified sodium lignin sulfonate is prepared according to the following method: dispersing the sodium lignin sulfonate in deionized water, adding sodium hydroxide solution to adjust and maintain the solution pH value to 11-12, increasing the solution temperature to 80-85°C, adding a quaternary ammonium agent, stirring and reacting for 4-5 hours to obtain a pre-reaction solution; lowering the temperature of the pre-reaction solution to 20-30°C, introducing carbon disulfide, and stirring for 30-60 minutes, then increasing the temperature to 50-60°C, stirring and reacting for 2-3 hours, cooling and dialysis, and then freeze-drying to obtain the quaternary ammonium modified sodium lignin sulfonate.

[0027] By adopting the above technical scheme, sodium lignin sulfonate contains a large number of functional groups such as alcohol hydroxyl, phenolic hydroxyl, carboxyl, sulfonic acid, etc. Under alkaline conditions, these groups containing active hydrogen can react with quaternary ammonium agents to introduce positively charged quaternary ammonium groups, so that sodium lignin sulfonate has amphoteric properties, which helps to form stronger electrostatic repulsion and steric hindrance and improve dispersibility.

[0028] Furthermore, under alkaline conditions, the hydroxyl groups in sodium lignin sulfonate can undergo a nucleophilic substitution reaction with carbon disulfide, and the intermediate formed is further rearranged, and finally a dithiocarboxyl group is introduced into the molecular chain of sodium lignin sulfonate, which improves the dispersibility and plays a role in reducing and fixing manganese ions. The prepared dispersant has good dispersibility and stability, and can control the growth and distribution of ferromanganese phosphate particles, and finally obtains a doped ferromanganese phosphate precursor with uniform particle size and uniform distribution, thereby improving the conductivity and rate performance of the positive electrode material.

[0029] In a second aspect, the present invention provides a doped ferromanganese phosphate precursor, which is prepared according to the above-mentioned method for preparing the doped ferromanganese phosphate precursor.

[0030] In a third aspect, the present invention provides a lithium manganese iron phosphate positive electrode material, which is prepared according to the following process steps:

[0031] S201. The doped ferromanganese phosphate precursor, the lithium source and the carbon source are ball-milled and mixed, and after the ball-milling, the mixture is dried to obtain a crude reaction product;

[0032] S202. The crude reaction product is sintered at 600-800° C. for 4-8 hours in an inert gas atmosphere, and finally cooled, crushed and sieved to obtain lithium manganese iron phosphate positive electrode material.

[0033] Preferably, the molar ratio of the lithium source to the phosphorus source is (0.95-1.1):1; and the added amount of the carbon source is 4-6% of the mass of the doped ferromanganese phosphate precursor.

[0034] Preferably, the lithium source includes one or more combinations of lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium hydroxide, lithium carbonate, lithium oxalate, lithium chloride, lithium acetate and lithium phosphate.

[0035] Preferably, the carbon source comprises a combination of one or more of starch, glucose, sucrose, corn flour, carbonate, citric acid, sodium acetate, polyethylene, polyethylene glycol and polyvinyl alcohol.

[0036] By adopting the above technical scheme, in the preparation process of the doped ferromanganese phosphate precursor, the dispersant used is quaternized modified sodium lignin sulfonate, which can be used as the first carbon source of the lithium ferromanganese phosphate positive electrode material to fix the ferromanganese phosphate precursor, control the particle morphology and inhibit the dissolution of manganese, thereby improving the diffusion rate of lithium ions; the carbon source added together with the lithium source is used as the second carbon source of the positive electrode material, coated on the surface of the lithium ferromanganese phosphate positive electrode material, which can increase the transmission path and transmission rate of electrons, thereby improving the conductivity of the positive electrode material, and the conductivity and rate performance of the lithium ferromanganese phosphate positive electrode material finally obtained are significantly improved.

[0037] Beneficial effects of the present invention:

[0038] 1. The ferromanganese phosphate precursor of the present invention is modified by vanadium ion doping, which can refine the grain size, significantly improve the diffusion rate of lithium ions, and show excellent rate performance; and through the electronic compensation mechanism, the electronic conductivity of the material is improved.

[0039] 2. In the present invention, quaternary ammonium modified sodium lignin sulfonate is used as a dispersant. The amphiphilic characteristics after modification make the dispersant have stronger electrostatic repulsion and provide greater steric hindrance, which can effectively avoid the problem of precursor particles being easily agglomerated due to large degree of refinement caused by vanadium doping, effectively control particle growth and dispersion, and thus obtain a ferromanganese phosphate precursor with uniform particle size and uniform distribution. In addition, the molecular chain of quaternary ammonium modified sodium lignin sulfonate also contains dithiocarboxyl groups, which can reduce and fix manganese ions while improving dispersion stability, reduce manganese dissolution, and improve material cycle performance. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Preparation Example

[0042] Preparation Example 1: A quaternary ammonium modified sodium lignin sulfonate is prepared according to the following method:

[0043] Take 10g of sodium lignin sulfonate and disperse it in 250mL of deionized water, add 20% sodium hydroxide solution by mass to adjust and maintain the pH value of the solution at 12, increase the solution temperature to 85°C, add 7g of dodecyldimethylbenzylammonium chloride, and stir the reaction for 4h to obtain a pre-reaction solution;

[0044] The temperature of the pre-reaction solution was lowered to 25°C, 3 g of carbon disulfide was introduced, and stirred for 40 minutes, then the temperature was raised to 60°C, stirred and reacted for 2 hours, cooled and dialyzed, and then freeze-dried to obtain quaternary ammonium modified sodium lignin sulfonate.

[0045] Preparation Example 2, a quaternized modified sodium lignin sulfonate, is different from Preparation Example 1 only in that the added amount of dodecyl dimethyl benzyl ammonium chloride is 6 g, and the added amount of carbon disulfide is 3.5 g.

[0046] Preparation Example 3, a quaternary ammonium modified sodium lignin sulfonate, is different from Preparation Example 1 only in that the added amount of dodecyl dimethyl benzyl ammonium chloride is 8 g, and the added amount of carbon disulfide is 2.5 g.

[0047] Preparation Example 4, a quaternized modified sodium lignin sulfonate, is different from Preparation Example 1 only in that the added amount of dodecyl dimethyl benzyl ammonium chloride is 5 g.

[0048] Preparation Example 5, a quaternary ammonium modified sodium lignin sulfonate, is different from Preparation Example 1 only in that the added amount of dodecyl dimethyl benzyl ammonium chloride is 9 g.

[0049] Preparation Example 6, a quaternary ammonium modified sodium lignin sulfonate, is different from Preparation Example 1 only in that the amount of carbon disulfide added is 2 g.

[0050] Preparation Example 7, a quaternary ammonium modified sodium lignin sulfonate, is different from Preparation Example 1 only in that the amount of carbon disulfide added is 4 g.

[0051] Preparation Example 8, a quaternary ammonium modified sodium lignin sulfonate, prepared according to the following method:

[0052] Take 10g of sodium lignin sulfonate and disperse it in 250mL of deionized water, add 20% sodium hydroxide solution by mass to adjust and maintain the pH value of the solution at 12, increase the solution temperature to 85°C, add 7g of dodecyldimethylbenzylammonium chloride, stir and react for 4h, cool to room temperature, dialyze, and finally freeze-dry to obtain quaternary ammonium modified sodium lignin sulfonate.

[0053] Preparation Example 9, a modified sodium lignin sulfonate, prepared according to the following method:

[0054] Take 10g of sodium lignin sulfonate and disperse it in 250mL of deionized water, add 20% sodium hydroxide solution by mass to adjust and maintain the pH value of the solution at 12, pass 3g of carbon disulfide, and stir for 40min, then increase the temperature to 60℃, stir and react for 2h, and then filter, wash and dry to obtain modified sodium lignin sulfonate.

[0055] Example

[0056] Example 1: A lithium manganese iron phosphate positive electrode material is prepared according to the following process steps:

[0057] Preparation of ferromanganese phosphate precursor:

[0058] S101. 0.6 mol of ferric nitrate, 0.4 mol of manganese sulfate and 1 mol of ammonium dihydrogen phosphate were added to deionized water to prepare a first mixed solution;

[0059] S102. 32 g of the quaternized ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 and 0.03 mol of vanadium nitrate were added to deionized water to prepare a second mixed solution;

[0060] S103. Raise the temperature of the first mixed solution to 45°C, add the second mixed solution dropwise while stirring, stir and react for 2h, and then hydrothermally react at 200°C for 7h;

[0061] S104. The hydrothermal reaction product is filtered, washed and dried to obtain a ferromanganese phosphate precursor;

[0062] Preparation of lithium manganese iron phosphate positive electrode material:

[0063] S201. The doped ferromanganese phosphate precursor obtained above, 1 mol of lithium carbonate and sucrose were ball-milled, wherein the amount of sucrose added was 5% by mass of the doped ferromanganese phosphate precursor, and the ball-milled product was dried to obtain a crude reaction product;

[0064] S202. The crude reaction product is sintered at 750° C. for 6 hours in a nitrogen atmosphere, and finally cooled, crushed and sieved to obtain lithium manganese iron phosphate positive electrode material.

[0065] Example 2, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the molar ratio of diammonium phosphate, ferric nitrate, manganese sulfate, vanadium nitrate and lithium carbonate is 1:0.3:0.7:0.02:1.1.

[0066] Example 3, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the molar ratio of diammonium phosphate, ferric nitrate, manganese sulfate, vanadium nitrate and lithium carbonate is 1:0.7:0.3:0.04:0.95.

[0067] Example 4, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is 26 g.

[0068] Example 5, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is 38 g.

[0069] Example 6, a lithium manganese iron phosphate positive electrode material, differs from Example 1 only in that the quaternized modified sodium lignin sulfonate prepared in Preparation Example 1 is replaced with an equal amount of the quaternized modified sodium lignin sulfonate prepared in Preparation Example 2; and the amount of sucrose added is 4% of the mass of the doped manganese iron phosphate precursor.

[0070] Example 7, a lithium manganese iron phosphate positive electrode material, differs from Example 1 only in that the quaternized modified sodium lignin sulfonate prepared in Preparation Example 1 is replaced by an equal amount of the quaternized modified sodium lignin sulfonate prepared in Preparation Example 3; the amount of sucrose added is 6% of the mass of the doped manganese iron phosphate precursor.

[0071] Example 8, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is replaced by an equal amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 4.

[0072] Example 9, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is replaced by an equal amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 5.

[0073] Example 10, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is replaced by an equal amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 6.

[0074] Example 11, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is replaced by an equal amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 7.

[0075] Example 12, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the molar ratio of vanadium nitrate to diammonium phosphate is 0.05:1.

[0076] Example 13, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is 16 g.

[0077] Example 14, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is 48 g.

[0078] Comparative Example

[0079] Comparative Example 1, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is replaced by an equal amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 8.

[0080] Comparative Example 2, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is replaced by an equal amount of the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 9.

[0081] Comparative Example 3, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the quaternary ammonium modified sodium lignin sulfonate prepared in Preparation Example 1 is not added to the second mixed solution.

[0082] Comparative Example 4 is a lithium manganese iron phosphate positive electrode material, which is different from Example 1 only in that vanadium nitrate is not added to the second mixed solution.

[0083] Performance testing

[0084] Sample preparation: The lithium iron manganese phosphate positive electrode material obtained in the embodiment and the comparative example was mixed with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a mass ratio of 8:1:1, and 0.05 g / mL of N-methyl-2-pyrrolidone was added to dilute the slurry, and the mixture was ground and coated on an aluminum foil, and dried at 80°C for 24 h to obtain a positive electrode sheet. Under a nitrogen atmosphere, a 2032-type button battery was prepared using a lithium sheet as the negative electrode material, a polypropylene microporous membrane as the diaphragm, and 1 mol / L LiPF6 as the electrolyte.

[0085] 1. Rate performance test: In the voltage range of 2.0-3.8V, at a constant temperature of 25°C, the specific capacity of the sample battery was tested at different rates of 1C, 5C and 10C. The test results are shown in Table 1.

[0086] 2. Cycle performance test: In the voltage range of 2.0 ~ 3.8V, 1C rate, 25 ℃ constant temperature conditions, the sample battery charge and discharge cycle test, the cycle test number was 500 weeks, the test and calculation of the capacity retention rate before and after the cycle, the test results are shown in Table 2.

[0087]

[0088]

[0089] According to Table 1 and Table 2, in combination with Example 1 and Example 2 to Example 7, it can be seen that the specific capacity and capacity retention rate of Example 2 to Example 7 at different rates are not significantly different from those of Example 1, indicating that the rate performance, cycle performance and conductivity of Example 2 to Example 7 are not significantly different from those of Example 1. The reason is that the difference between Example 2 to Example 7 and Example 1 is only that the ratio of the raw materials is changed within the required range, which has little effect on the performance of the final lithium manganese iron phosphate positive electrode material.

[0090] Combining Example 1, Example 8 to Example 11, Comparative Example 1 and Comparative Example 2, it can be seen that the specific capacity and capacity retention rate of Example 8 to Example 11, Comparative Example 1 and Comparative Example 2 at different rates are reduced compared with Example 1, among which Comparative Example 1 and Comparative Example 2 are significantly reduced. The reason is that Examples 8 to 11 change the raw material ratio of the dispersant quaternized modified sodium lignin sulfonate. Specifically, the amount of quaternized agent added in Example 8 is reduced, the dispersion modification effect of sodium lignin sulfonate is reduced, and the agglomeration between the precursor particles will cause the electrochemical performance of the material to decrease. In Comparative Example 2, sodium lignin sulfonate is not quaternized, and the electrostatic repulsion and steric hindrance are significantly reduced, and the performance decrease is more obvious; in Example 9, the amount of quaternized agent added is increased, the surface activity is large, the attraction to the particles is large, which is not conducive to the refinement of the ferromanganese phosphate precursor particles, and the rate performance of the material is slightly reduced. In Example 10, the amount of carbon disulfide added was reduced, the content of dithiocarboxyl groups on the molecular chain of the quaternary ammonium modified sodium lignin sulfonate decreased, the reducing effect and fixing effect on manganese ions decreased, and the rate performance and cycle performance of the material decreased. In Comparative Example 1, the molecular chain of the quaternary ammonium modified sodium lignin sulfonate did not contain dithiocarboxyl groups, and the performance degradation was more obvious; in Example 11, the amount of carbon disulfide added was increased, and the increase in the content of dithiocarboxyl groups would rob the manganese ions in the ferromanganese phosphate precursor for complexation reaction, which is not conducive to the formation of the lattice of the ferromanganese phosphate precursor.

[0091] Combining Example 1 and Example 12, it can be seen that the specific capacity and capacity retention rate of Example 12 at different rates are lower than those of Example 1. The reason is that the content of vanadium ion doping is increased in Example 12, which will lead to a decrease in the proportion of tetravalent vanadium ions in the system. The reduction of high-valent vanadium ions will affect the doping process, reduce the diffusion rate of lithium ions, and reduce the conductivity of the positive electrode material, thereby causing the rate performance and cycle performance of the material to decrease.

[0092] Combining Example 1, Example 13, Example 14 and Comparative Example 3, it can be seen that the specific capacity and capacity retention rate of Example 13 and Example 14 at different rates are reduced compared with Example 1, and the reduction in Comparative Example 3 is more obvious. The reason is that the difference between Example 13 and Example 14 compared with Example 1 is only the amount of dispersant added. In Example 13, the amount of dispersant added is reduced, and the dispersibility between the particles of the ferromanganese phosphate precursor decreases during the preparation process, and agglomeration occurs, resulting in non-uniform particle size and uneven distribution of the positive electrode material particles, which in turn causes a decrease in material performance. In Comparative Example 3, no dispersant is added, and the agglomeration phenomenon of the vanadium-doped ferromanganese phosphate precursor is more serious, and the performance degradation is more obvious; in Example 14, the amount of dispersant added is increased, and the increase in the dispersant content will affect the particle refinement process during the precursor preparation process, resulting in a decrease in material performance.

[0093] Combining Example 1 and Comparative Example 4, it can be seen that the specific capacity and capacity retention rate of Comparative Example 4 at different rates are significantly reduced compared with those of Example 1. The reason is that the manganese iron phosphate precursor in Comparative Example 4 is not doped with vanadium ions, the diffusion rate of lithium ions is significantly reduced, and the particle size of the manganese iron phosphate lithium positive electrode material is also increased, resulting in a significant decrease in the rate performance, cycle performance and conductivity of the positive electrode material.

[0094] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0095] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a doped ferromanganese phosphate precursor, characterized in that: The process steps include: S101. Adding an iron source, a manganese source and a phosphorus source to deionized water to form a first mixed solution; S102. Adding the dispersant and the vanadium source to deionized water to prepare a second mixed solution; S103. Raise the temperature of the first mixed solution to 40-45°C, add the second mixed solution dropwise while stirring, stir and react for 1-2 hours, and then hydrothermally react at 180-220°C for 6-7 hours; S104. The hydrothermal reaction product is filtered, washed and dried to obtain a ferromanganese phosphate precursor; The dispersant is quaternary ammonium modified sodium lignin sulfonate; the molecular chain of the quaternary ammonium modified sodium lignin sulfonate contains dithiocarboxyl groups.

2. The method for preparing a doped ferromanganese phosphate precursor according to claim 1, characterized in that: The molar ratio of the phosphorus source, iron source, manganese source and vanadium source is 1: (0.3-0.7): (0.3-0.7): (0.02-0.04).

3. The method for preparing a doped ferromanganese phosphate precursor according to claim 1, characterized in that: The vanadium source includes one or more of vanadium nitrate, vanadium pentoxide, ammonium metavanadate, vanadium chloride, sodium orthovanadate and hydrated vanadyl sulfate.

4. The method for preparing a doped ferromanganese phosphate precursor according to claim 1, characterized in that: The added amount of the dispersant is 8-12% of the total mass of the iron source, the manganese source and the phosphorus source.

5. The method for preparing a doped ferromanganese phosphate precursor according to claim 1, characterized in that: The raw materials of the quaternized modified sodium lignin sulfonate include sodium lignin sulfonate, a quaternary ammonium agent and carbon disulfide in a mass ratio of 1: (0.6-0.8): (0.25-0.35).

6. The method for preparing a doped ferromanganese phosphate precursor according to claim 5, characterized in that: The quaternizing agent is a combination of one or more of 3-chloro-2-hydroxypropyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride and hexadecyltrimethylammonium bromide.

7. The method for preparing a doped ferromanganese phosphate precursor according to claim 5, characterized in that: The quaternary ammonium modified sodium lignin sulfonate is prepared according to the following method: dispersing the sodium lignin sulfonate in deionized water, adding a sodium hydroxide solution to adjust and maintain the pH value of the solution to 11-12, increasing the solution temperature to 80-85° C., adding a quaternary ammonium agent, stirring and reacting for 4-5 hours to obtain a pre-reaction solution; lowering the temperature of the pre-reaction solution to 20-30° C., introducing carbon disulfide, stirring for 30-60 minutes, then increasing the temperature to 50-60° C., stirring and reacting for 2-3 hours, cooling and dialysis, and freeze-drying to obtain the quaternary ammonium modified sodium lignin sulfonate.

8. A doped ferromanganese phosphate precursor, characterized in that: The doped manganese ferrophosphate precursor is prepared according to the method for preparing the doped manganese ferrophosphate precursor according to any one of claims 1 to 7.

9. A lithium manganese iron phosphate positive electrode material, characterized in that: It is prepared according to the following process steps: S201. The doped ferromanganese phosphate precursor, the lithium source and the carbon source according to claim 8 are ball-milled and mixed, and dried after the ball-milling to obtain a crude reaction product; S202. The crude reaction product is sintered at 600-800° C. for 4-8 hours in an inert gas atmosphere, and finally cooled, crushed and sieved to obtain lithium manganese iron phosphate positive electrode material.

10. A lithium iron manganese phosphate positive electrode material according to claim 9, characterized in that: The molar ratio of the lithium source to the phosphorus source is (0.95-1.1):1; the added amount of the carbon source is 4-6% of the mass of the doped ferromanganese phosphate precursor.

Citation Information

Patent Citations

  • Lignin / titanium dioxide hybrid composite nanomaterial as well as preparation method and application thereof

    CN113025073A

  • Fluorine-doped lithium iron manganese phosphate positive electrode material and preparation method thereof

    CN114373912A